ANALISIS POLA CURAH HUJAN DI PAPUA BARAT DAYA: Bahasa Indonesia - Melinda, Shelin; Pancariniwati, Sri; Maulana, Wahyu Taqwa; Wibowo, Krisnadi Pandu (LRI Universitas Muhammadiyah Sorong, 2025)
The province of Southwest Papua is characterized by its mountainous terrain, which influences the region's precipitation patterns. The typical rainfall distribution in this area takes on an